The haustorium: The root of biotrophic fungal pathogens - Mapuranga, Johannes; Zhang, Lirong; Zhang, Na; Yang, Wenxiang (Frontiers in Plant Science, 2022)
One of the primary causes of agricultural losses is biotrophic plant pathogenic fungi. The haustorium is a sophisticated infection structure of the biotrophic fungal plant pathogens essential for nutrient acquisition from the host as well as effector protein secretion and delivery of the effectors into the host. The haustorium is separated from the invaginated membrane by an interfacial matrix. Relatively, few pathogenicity genes associated with biotrophy have been found. This review provides an overview of the haustorium structure and functions, including the most recent haustorial transcriptome studies. Although molecular studies have greatly improved our knowledge of this structure, there are still several questions to be answered in this area.